1994
DOI: 10.1001/jama.1994.03520100049032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Recent Previous Visit to a Physician on Outcome After Childhood Bacterial Meningitis

Abstract: Children who had visited a physician the previous day or 2 to 4 days before meningitis was diagnosed did not exhibit an increased frequency of hearing impairment, other neurologic abnormalities, or overall adverse outcome compared with children whose meningitis was diagnosed at once.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…25 26 The main contribution to outcome was postulated to be the severity of disease, with slowly evolving cases more likely to be diagnosed late. 25 26 We found that delayed hospital admission did not predict the combined variable of death or severe neurological sequelae. However, when deaths were excluded, delayed hospitalisation significantly predicted morbidity in survivors.…”
Section: Discussionmentioning
confidence: 70%
“…25 26 The main contribution to outcome was postulated to be the severity of disease, with slowly evolving cases more likely to be diagnosed late. 25 26 We found that delayed hospital admission did not predict the combined variable of death or severe neurological sequelae. However, when deaths were excluded, delayed hospitalisation significantly predicted morbidity in survivors.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that between one-quarter and one-half of all children who develop ABM have visited a clinician prior to having ABM diagnosed [8,9]. In our study, 45% of young children sought care from a clinician prior to the diagnosis of meningitis, and 64% of the children who visited a clinician did so within 24 h of the onset of fever.…”
Section: Discussionmentioning
confidence: 59%
“…Kallio et al [8] reported that between 44% and 58% of patients had received prior antibiotic treatment, depending on the length of time between the last contact with a clinician and the visit at which a diagnosis of meningitis was made. Other studies have reported a total rate of antibiotic use (not restricted to patients who visit a clinician) of up to 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality of patients presenting with meningococcal meningitis is low (1%–5%), considerably lower than that of patients with invasive meningococcal disease without meningitis (up to 40%). Furthermore, prognosis of patients with bacterial meningitis (from all causes) was no worse in those whose disease was not recognised for as long as two to four days before admission than in those admitted when first seen 7 …”
Section: Syndromes Of Meningococcal Diseasementioning
confidence: 99%